The Facelessness of Individuals and Speechlessness of the Communities: Literary Evidences Exposing Human Suffering in an Island Nation - Shriganeshan, K. (An International Multidisciplinary Double-Blind Peer-reviewed Research Journal, 2019)
This paper looks into the problems highlighted by Tamil writers whose short stories appeared in the anthology titled Tamil Short Stories from Sri Lanka, the first-ever collection from Sri Lanka (English translation by S.Pathmanathan) and the way they treat their themes. Sri Lankan Tamil writers do continue to write about the people’s struggle and suffering which did not go beyond confines of the Tamil. A selection of stories which are well represented with Sri Lankan multi-cultural and multi-lingual identity, translated and published for the rest of the world in 2013 speaks a lot about the underlying political, social and cultural issues, facelessness of individuals and speechlessness of the communities, strengths and weaknesses, ambitions and failures, and forms of political oppression and marginality. A move from a realist mode of writing style to a narrative mode with a surreal quality is also observed in the stories which aptly, sometimes shift to a symbolist style in order to provide a political voice and interpretation in an otherwise suppressed atmosphere.
Keywords: Facelessness; Individuals; Speechlessness; Communities; Suffering